Evaluation of knowledge, attitude, and perception of pictograms in improving understanding of foreign medicine packages and leaflets among Malaysians / John Kwong Siew Shia ... [et al.] - Kwong, John Siew Shia; Muhamad Zainal Abidin, Nurul Athirah; Abdul Razak, Mohamed Razeef; Jalaludin, Nadia; Mohd Rocky, Nik Ateerah Rasheeda; Hussin, Siti Nooraishah (UiTM Press, 2024)
Access to foreign medicines is now more prevalent due to globalization and international travel. However, understanding the labels and content of these medications can be challenging due to the language barrier. Pictograms are visual representations of words or phrases, that can be used on foreign medicinal packages and leaflets to ensure the correct usage of the medications. This study aims to explore the knowledge, attitude, and perception of pictograms in improving the understanding of foreign medicine packages and leaflets among the Malaysian population. Methods: This was a cross- sectional study with stratified random convenience sampling. A total of 397 Malaysian respondents participated in this study. A set of questionnaires was distributed using the Google Forms platform. The scores on knowledge, attitude, and perception were assessed based on previous studies by Bloom's cut- off point criteria. SPSS version 28.0 was used to analyze the data.